Time-Dependent Expression of Arc and Zif268 after Acquisition of Fear Conditioning. (26th May 2010) - Lonergan, Mary E.; Gafford, Georgette M.; Jarome, Timothy J.; Helmstetter, Fred J.
Abstract : Memory consolidation requires transcription and translation of new protein. Arc, an effector immediate early gene, and zif268, a regulatory transcription factor, have been implicated in synaptic plasticity underlying learning and memory. This study explored the temporal expression profiles of these proteins in the rat hippocampus following fear conditioning. We observed a time-dependent increase of Arc protein in the dorsal hippocampus 30-to-90-minute post training, returning to basal levels at 4 h. Zif268 protein levels, however, gradually increased at 30-minute post training before peaking in expression at 60 minute. The timing of hippocampal Arc and zif268 expression coincides with the critical period for protein synthesis-dependent memory consolidation following fear conditioning. However, the expression of Arc protein appears to be driven by context exploration, whereas, zif268 expression may be more specifically related to associative learning. These findings suggest that altered Arc and zif268 expression are related to neural plasticity during the formation of fear memory.